Implementasi Algoritme Kriptografi Lizard untuk Mengamankan Pengiriman Data Menggunakan Arsitektur Web Service REST pada Mikrokontroler NodeMCU - Kalbuadi Joyoputro; Ari Kusyanti; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
There are three elements of security, which are data confidentiality, data integrity, and data availability. This research focuses data confidentiality on NodeMCU microcontroller device in an IoT environment. Relatively small NodeMCU processor and dynamic memory becomes a challenge in fulfilling the data confidentiality. Lizard stream cipher algorithm is implemented on NodeMCU. The JSON (JavaScript Object Notation) data will be encrypted into a cipher text using the Lizard algorithm keystream before being sent to the database server over the wireless wifi network. On the server side, the data will be decrypted into its original form and stored into the database. The process of sending data uses the REST (Representational State Transfer) web service architecture. There are four parts of testing to ensure the system has been running well, that is test vector validation testing, functional testing, time and memory performance testing, and security testing. The 216 and 352 bit keystream generated on NodeMCU devices takes 0.01 seconds and 3.4% of total dynamic memory, while encrypting 216 and 352 bits plain text takes 0.02 and 0.04 seconds with 0.3% of total dynamic memory. Implementation of Lizard algorithm has successfully guaranteed the data confidentiality.